Structure and Openness in Literary Semiotics: A Comparative Study of Greimas, Eco, and Barthes - Amraj, M. Akbar Kurtubi (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This article offers a comparative analysis of three foundational figures in literary semiotics: Algirdas Julien Greimas, Umberto Eco, and Roland Barthes. Drawing on the philosophical traditions of Hegel, Kant, and Nietzsche, the study examines how each theorist articulates distinct approaches to textual meaning, structure, and interpretation. Greimas develops a rationalist framework centered on structural semantics and coherence; Eco positions himself between rationalism and postmodern multiplicity by proposing a model of textual openness constrained by interpretive competence; and Barthes advocates for the primacy of the signifier and the aesthetics of polysemy, resisting conceptual closure through a Nietzschean lens. Methodologically, the article employs close reading and comparative conceptual analysis to highlight epistemological tensions and intersections among the three thinkers. Ultimately, the study maps the evolution of literary semiotics as a dynamic dialogue between structure and openness, coherence and ambiguity, authorial intention and readerly participation